Market Overview of Indonesia Copper Export Commodity (Case of Indonesia, Thailand, and Japan Copper Exporting Countries in 2004-2018) - Greatty Claudia; Iman Murtono Soenhadji (Journal Research of Social Science, Economics, and Management, 2021)
The purpose of this study is to analyze developments, measure the level of trade specialization, and explore the story of competitiveness of Indonesia, Thailand, and Japan copper commodity exports in the world market. The analytical methods used are TSI (Trade Specialization Index), RCA (Revealed Comparative Advantage), RCTA (Revealed Comparative Trade Advantage), and AR (Acceleration Ratio). The results showed that Indonesia's copper exports and Indonesian specialization level towards Thailand were at the Maturity stage because the average obtained was 0.910. But for Indonesia, Japan for -0,462 and Thailand for Japan, -0,385 are in the Import Substitution stage, and for Indonesia, itself is in the Growth stage with an average of 0.792. As for the RCA results, Indonesia is the most superior because it has an RCA value of> 1 as much as 15, followed by Thailand with an RCA> 1 as much as three, which means that Indonesia has a comparative advantage over the world market and Thailand also has good competitiveness, but for Japan, it does not have an RCA> 1 which means it has no comparative advantage to the world market. The RCTA results show that Indonesia has high competitiveness against the world market because it has had a positive index result for 15 years. AR results show that Indonesia and Japan can seize the copper export market to the world market, while for Thailand for the past three years, namely in 2016-2018.